Análisis del impacto de un sistema contable en la eficiencia del registro de ingresos y egresos - Rubio Funez, Solange Paulina (2024)
This study analyzes the impact of implementing an automated accounting system on the efficiency of income and expense recording in a commercial company in Guayaquil dedicated to selling home decoration items. The current manual system was found to have significant deficiencies, such as frequent errors and variability in recording times, which negatively affect the company's financial management. Through a mixedmethods research approach, including surveys and interviews, it was concluded that automating the accounting system could significantly improve accuracy, reduce transaction recording time, and increase the transparency of financial records, all of which are essential for strategic decision-making. Recommendations include implementing an automated accounting system, training staff, and continuously monitoring the new system to ensure its effectiveness and efficiency.